Review of nursing care for patients undergoing percutaneous coronary intervention: a patient journey approach - Rolley, John; Davidson, Patricia; Salamonson, Y.; Fernandez, R.; Dennison, C. (Blackwell Publishing, 2009)
Aim: To evaluate the existing literature to inform nursing management of people undergoing percutaneous coronary intervention.Background: Percutaneous coronary intervention is an increasingly important revascularisation strategy in coronary heart disease management and can be an emergent, planned or rescue procedure. Nurses plan a critical role in delivering care in both the independent and collaborative contexts of percutaneous coronary intervention management.Design: systematic review.Method: The method of an integrative literature review, using the conceptual framework of the patient journey, was used to describe existing evidence and to determine important areas for future research. The electronic data bases CINAHL, Medline, Cochrane and the Joanna Briggs data bases were searched using terms including: (angioplasty, transulminal, percutaneous coronary), nursing care, postprocedure complications (haemorrhage, ecchymosis, haematoma), rehabilitation, emergency medical services (transportation of patients, triage).Results: Despite the frequency of the procedure, there are limited data to inform nursing care for people undergoing percutaneous coronary intervention. Currently, there are no widely accessible nursing practice guidelines focusing on the nursing management in percutaneous coronary intervention. Findings of the review were summarised under the headings: Symptom recognition; Treatment decision; Peri-percutaneous coronary intervention care, describing the acute management and Post-percutaneous coronary intervention management identifying the discharge planning and secondary prevention phase.Conclusions: Cardiovascular nurses need to engage in developing evidence to support guideline development. Developing consensus on nurse sensitive patient outcome indicators may enable benchmarking strategies and inform clinical trial design. Relevance to clinical practice: To improve the care given to individuals undergoing percutaneous coronary intervention, it is important to base practice on high-level evidence. Where this is lacking, clinicians need to arrive at a consensus as to appropriate standards of practice while also engaging in developing evidence. This must be considered, however, from the central perspective of the patient and their family.